2016
DOI: 10.1002/prot.25095
|View full text |Cite
|
Sign up to set email alerts
|

Novel proteases from the genome of the carnivorous plant Drosera capensis: Structural prediction and comparative analysis

Abstract: In his 1875 monograph on insectivorous plants, Darwin described the feeding reactions of Drosera flypaper traps and predicted that their secretions contained a “ferment” similar to mammalian pepsin, an aspartic protease. Here we report a high-quality draft genome sequence for the cape sundew, Drosera capensis, the first genome of a carnivorous plant from order Caryophyllales, which also includes the Venus flytrap (Dionaea) and the tropical pitcher plants (Nepenthes). This species was selected in part for its h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 87 publications
1
34
0
Order By: Relevance
“…Several other significantly enriched GOs are associated with this gene family. Cysteine proteases have been identified as major functional components of Venus flytrap (Dionaea muscipula) digestive fluid (72), reported in three D. muscipula transcriptomes (70,73,74), and structurally annotated for both Cape sundew (Drosera capensis) draft genome sequences (75,76) and D. muscipula (77). We found tandem clusters of homologous proteaseencoding genes in the U. gibba genome that had demonstrably undergone tandem duplication both before and after the most recent WGD event in U. gibba's evolutionary history (Fig.…”
Section: Significancementioning
confidence: 91%
“…Several other significantly enriched GOs are associated with this gene family. Cysteine proteases have been identified as major functional components of Venus flytrap (Dionaea muscipula) digestive fluid (72), reported in three D. muscipula transcriptomes (70,73,74), and structurally annotated for both Cape sundew (Drosera capensis) draft genome sequences (75,76) and D. muscipula (77). We found tandem clusters of homologous proteaseencoding genes in the U. gibba genome that had demonstrably undergone tandem duplication both before and after the most recent WGD event in U. gibba's evolutionary history (Fig.…”
Section: Significancementioning
confidence: 91%
“…have reported usage for dressing wounds and as a remedy for urinary infections and cough (Patel, 2014). To date, Genlisea aurea (Leushkin et al, 2013) and Utricularia gibba (Lan et al, 2017) are among the four carnivorous plants with genome sequences publicly available, apart from Drosera capensis (Butts, Bierma & Martin, 2016) and Cephalotus follicularis (Fukushima et al, 2017). The availability of genome sequences has contributed greatly to enzyme discovery and improving our understanding of carnivory mechanisms and evolution in different carnivorous plant families.…”
Section: Different Families Of Carnivorous Plantsmentioning
confidence: 99%
“…They often feed on microscopic and perform digestive functions in closed traps. Thus, they are less vulnerable to the environmental constraints in exposed environments (Butts et al, 2016). The genome sequencing results showed that the genome size difference between G. aurea and U. gibba was more than one time, 43 Mb vs 101 Mb.…”
Section: Introductionmentioning
confidence: 99%